PELESTARIAN KLIPING SURAT KABAR KOLEKSI PERPUSTAKAAN CENTRE FOR STRATEGIC AND INTERNATIONAL STUDIES (CSIS) : Pelestarian Kliping Surat Kabar Koleksi Perpustakaan Centre For Strategic And International Studies - damaji ratmono (Universitas Pendidikan Ganesha, 2022)
Abstract Newspaper clipping activities have been carried out by CSIS (Centre for Strategic and International Studies) since 1971. This national and international institution located on Jalan Tanah Abang, Central Jakarta, for approximately 50 (fifty) years has collected at least 10,000 (ten thousand) ) the title of the clipping. The clippings were arranged using the ordnere method and stored on storage shelves in the library room. Gradually, the collection of clippings was damaged due to age, even though the contents of the news from the collection of clippings were still needed by researchers at CSIS to support their research. Based on observations, condition surveys, and interviews that the authors did at CSIS, the effort to save these collections of clippings is done by using physical preservation and information preservation methods. Physical preservation is carried out by the method of binding library materials, while information preservation is carried out by transferring media into other forms. By carrying out these conservation efforts, it can save and extend the life of the clipping collection in the CSIS library so that the information contained in it can be utilized by researchers at CSIS. Keywords: clipping, CSIS library, preservation, binding library materials, transfer of information media